Studying the estimation levels of inflammatory markers and NF-κB in MDR and DS-TB patients - Yassmeen A. Hussain,; Khairallah A. S. Mohammed,; Naael H. Ali, (University of Thi-Qar Journal of Science, 2023)
Tuberculosis (TB) is one of the most infectious and deadly diseases, especially after the emergence of drug-resistant bacteria. Therefore, in this study, we developed a method to evaluate the ability of using CXCL10, CXCL9, MMP9, suPAR and the expression gene (NF-κB) and their rolesin the diagnosis and treatment of the disease in patients. Also, we used ELISA and qPCR techniques to compare the serum levels of CXCL10, CXCL9, MMP9, suPAR and NF-κB gene in drug resistant and drug sensitive TB. The serum levels of CXCL10, CXCL9, MMP9, suPAR and the expression of NF-κB gene was compared among drug resistant and drug sensitive TB using ELISA and qPCR Techniques, respectively. Our results showed an increasing in the serum levels of CXCL10, CXCL9 and suPAR, in the drug resistant of TB patients but not in the drug sensitive group, however, all of them did not reach the significant level, it was found that expression of NF-κB in drug sensitive group was higher (3.22-fold) than that in the drug resistant-TB patients (2.70-fold).